PERSEPSI PETANI TERHADAP PENGGUNAAN PUPUK ANORGANIK PADA TANAMAN HORTIKULTURA DI DESA MATA AIR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Felisitas Nau Bay; Leta Rafael Levis; Maria Bano (Buletin Ilmiah Impas, 2022)
This study aims to determine how farmers' perceptions of the use of inorganic fertilizers on horticultural crops in Mata Air Village, Central Kupang District, Kupang Regency. This research was conducted from November to December 2020. This research was conducted using a survey method. Determination of the location of the study was done intentionally (purposive sampling) with the consideration that in the village of Mata Air is one of the villages producing horticultural crops. The population in this study were members of the Mata Air Village Farmers Group who were active in horticultural farming which included 56 respondent farmers. Sampling technique using a simple random method (Sample Random Sampling). The type of data used is primary data obtained from horticultural farmers by conducting direct interviews. Secondary data is data collected from relevant agencies, literature searches, research reports, the Central Bureau of Statistics (BPS), articles and the internet. To answer the first objective, the data were analyzed using descriptive analysis using a Likert scale. The results showed that Farmers' Perceptions of the use of inorganic fertilizers on horticultural crops in Mata Air Village had six elements of perception, namely: the level of relative advantage, the level of difficulty, the level of complexity, the level of ease of dicoa, the level of ease of seeing the results, and productivity in the category of satisfied with the score. the average obtained is 3.82 and the highest score percentage of the average score is 76%.